Keluarga Beda Agama dan Implikasi Hukum Terhadap Anak - Muhammad Adi Suseno; Lina Kushidayati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
This article aims to find out the causes of different religions in the family at Dukuh Ngelo Karangrowo Undaan Kudus and the legal implications for children born into different religions in terms of Islamic law. This research is included in the category of field research using a qualitative approach method. Sources of data used in this study are primary data and secondary data. Primary data is obtained from interviews with various informants, while secondary data is in the form of laws and regulations, books, journal articles and others. The results and conclusions of this study indicate that the occurrence of different religions in the family at Dukuh Ngelo Karangrowo Invite Kudus is due to interfaith marriages that do not consider the legal aspects it causes, especially in terms of the inheritance of children born as a result of their marriage. The legal implication for biological children born to interfaith couples in the Islamic perspective is that children are prevented from obtaining inheritance from their parents so that grants are a solution for children to get justice for their parents' assets.    AbstrakArtikel ini bertujuan untuk mengetahui penyebab berbedanya agama dalam keluarga di Dukuh Ngelo Karangrowo Undaan Kudus dan implikasi hukum terhadap anak yang dilahirkan dalam keluarga beda agama ditinjau dari hukum Islam. Penelitian ini termasuk dalam kategori penelitian lapangan dengan menggunakan metode pendekatan kualitatif. Sumber data yang digunakan dalam penelitian adalah data primer dan data sekunder. Data primer didapatkan dari wawancara dengan berbagai informan, sedangkan data sekunder berupa peraturan perundang-undangan, buku, artikel jurnal dan lain-lain. Hasil dan sekaligus simpulan dari penelitian ini menunjukkan bahwa terjadinya beda agama dalam keluarga di Dukuh Ngelo Karangrowo Undangan Kudus disebabkan karena perkawinan beda agama yang tidak memandang dari aspek hukum yang ditimbulkannya terutama dalam hal kewarisan terhadap anak yang dilahirkan hasil perkawinannya. Implikasi hukum bagi anak kandung yang dilahirkan dari pasangan beda agama dalam perspektif Islam adalah anak terhalang untuk mendapatkan warisan dari orang tuanya sehingga hibah menjadi solusi bagi anak untuk mendapatkan keadilan atas harta orang tuanya.